Communication Accommodation of the Kiai in the Effort to Acculturate Islamic Culture at Pondok Pesantren Az-Zahrowiyah Perigi, Tambelangan, Sampang - Ahmad In'am Kholifi; Nikmah Suryandari; Farida Nurul Rahmawati (Green Publisher Indonesia, 2026)
Amid the social life of the Madurese community, the acculturation between local traditions and Islamic values continues to unfold at Pondok Pesantren Az-Zahrowiyah Perigi, Tambelangan, Sampang. In this process, the Kiai serves not only as a religious leader but also as a communicator and mediator who maintains the balance between local culture and Islamic teachings. This study aims to provide an in-depth description of the communication strategies employed by the Kiai in managing this acculturation within the pesantren environment. This research uses a qualitative method with a descriptive approach through in-depth interviews, participatory observation, and documentation. Data analysis was conducted through reduction, data display, and conclusion drawing to identify patterns and strategic meanings within the Kiai’s communication practices in the daily life of the students and the surrounding community. The outputs of this study include a research proposal, a final MBKM Research report, an activity logbook, and a draft scientific article targeted for publication in an accredited national journal. The findings indicate that the Kiai’s communication strategies are accommodative, adaptive, and humanistic, enabling him to mitigate cultural conflicts, shape students’ behavior, and maintain harmony between Madurese local values and Islamic principles. This research underscores that the success of cultural acculturation in pesantren is strongly influenced by the Kiai’s communicative ability to guide, calm, and unite the community.